The effect of salmonella pullorum on broiler chicken in Iraq - Rusul Ghazi Hawal; Mushtaq Talib Bakr (Zien Journals, 2022)
Salmonella pullorum is classified under serogroup D, with Salmonella gallinarum and other organisms like Salmone enteritidis,S. typhi and S. dublin. PD is a major threat to poultry production in developing countries. IL-6 plays a key role in both the body's innate defenses and the maturation of the adaptive immune system. The mortality rate for PD in chicks can reach 100%, peaking between the ages of two and three weeks. Serological testing may be utilized to determine whether a flock is infected. Adaptive and innate immune mechanisms play important roles in the body's ability to defend against various pathogens. Clinical signs could include decreased feed intake, huddling close to heat sources, and diarrhea. Good hygiene, biosecurity, serological testing, and slaughter regulations are all necessary to eliminate Salmonella. result after 10 days after exposure to an infection, the mortality is highest in the third and fourth groups of chicks. Anorexia, diarrhea, dehydration, depression, huddling, ruffled feathers, weakness, decreased feed consumption, decreased feeding and pasting of the vent feathers are some of the clinical signs that were noted throughout the experimental period. Young birds are especially susceptible to S. pullorum colonization, which can result in either a severe clinical illness or a disease-free persistence of infection. Both the kidney and liver were impacted by S. pullorum in 2-day-old chickens. the liver primary lymphoid tissues where bacteria located and grow showed the most severe histopathological abnormalities. Microscopically the lesions in the liver, kidney, were less severe in (G1 and G4) compared to (G2and G3).
Keywords: salmonella pullorum; liver; kidney